Skin manifestations of peripheral artery disease: Prevalence and diagnostic utility - Ejiroghene Martha Umuerri (Journal of Clinical and Preventive Cardiology, 2019)
Introduction: Peripheral artery disease (PAD) is a common but underdiagnosed arm of the cardiovascular triad. Reliance on the presence of skin manifestations of chronic lower limb ischemia may result in clinical inertia in the diagnosis of PAD. Objective: Literature on the skin manifestations of PAD is limited. This paper aims to determine the prevalence and diagnostic value of skin manifestations of PAD. Methods: This was a cross-sectional descriptive study of consecutive adults with hypertension and diabetes attending the consultant medical outpatient department, University of Benin Teaching Hospital, Benin-city, Nigeria. Physical examination of the skin of the lower limbs for features suggestive of PAD and ankle-brachial index (ABI) were performed. A diagnosis of PAD was made if ABI < 0.9. Results: Of the 541 participants, 115 (21.3%) had skin changes suggestive of PAD, and 182 (33.6%) had low ABI < 0.9. Among participants with PAD, 65 (35.7%) had skin manifestations suggestive of PAD. The association between PAD and skin manifestations suggestive of PAD was significant (χ2 = 34.248,P < 0.001). The sensitivity, specificity, positive, and negative predictive values of the presence of skin manifestations as a diagnostic tool for PAD compared with low ABI was 35.7%, 86.1%, 56.5%, and 72.5%, respectively. Conclusion: Among participants with PAD, the prevalence of skin manifestations of suggestive of PAD was 35.7%. Reliance on the presence of skin changes for diagnosis of PAD may result in missed or delayed diagnosis because of its low sensitivity and positive predictive value.